The usefulness of an optical monitor for the assessment of human exposure to fine dust in indoor air - Małgorzata Kowalska; Anna Mainka; Walter Mucha (Nofer Institute of Occupational Medicine, 2019)
Background An important issue in the assessment of health risks related to air pollution with fine dust is the measurement of individual exposure. Such possibilities are provided by relatively easy to use optical monitors. The aim of the presented work was to assess the possibility of using the AM520 optical monitor to measure individual human exposure to PM 2.5 and PM 10 indoors by determining the calibration factor and assessing the compliance of the measurement with the reference method. Material and Methods As part of the research, indoor concentrations of PM 2.5 and PM 10 and were measured (3 locations in the Gliwice Poviat, March−May 2017) with the use of the SidePak Personal Aerosol Monitor AM520, as well as the reference LVS3D device by means of the gravimetric method. The value of the calibration coefficient for the optical monitor was determined, and the consistency of measurements performed with both methods was assessed. Results The photometric calibration factor ranged 0.33−0.40 and was concurrent with the 0.38 value recommended by the manufacturer. The determination coefficient for the correlation between the measurement results obtained with the optical and gravimetric methods was very high (R 2 = 0.91). Conclusions The presented results are promising and allow for the conclusion that the AM520 optical monitor can be used to assess individual exposure to PM 2.5 and PM 10 indoors. Med Pr. 2019;70(2):213-20